Karakterisktik Hidrodinamika dan Aerodinamika Pesawat WISE L8 Pada Saat Hydro Planing dan Mengudara Berdasarkan Perhitungan CFD - Sayuti Syamsuar (Research and Development Agency of The Ministry of Transportation, 2018)
The Hydrodynamic and Aerodynamic Characteristics of WISE L8 During Hydro Planing and Airborne Base On CFD: This paper explains why the computational fluid dynamics is used on the model 3-D CATIA of Wing in Surface Effect craft WISE Lippisch configuration 8 seaters capacity for medium and high-speed conditions during hydro planing and airborne. The analysis stage on the calculation used the k-ε model turbulence with 1,690,862 mesh consists of 4 stages procedures that are ICEM, preprocessor, solver and convergence. On each programming stage that are gave the nominal value results. On this paper, there are showed the results of even keel and trimmed condition by using Savitsky method where the changes of trim angle τ (t) are being influence the hydrodynamic drag and total hydrodynamic force versus airspeed results. Based on this research, that propose for the Pilot using trim angle variation during takeoff procedure. Paper ini menjelaskan mengapa diperlukan penggunaan programkomputasional dinamika fluida CFD terhadap model 3-D CATIA dari pesawat WISE L8 untuk kondisi kecepatan medium dan tinggi saat hydro planing dan mengudara. Pada proses perhitungan yang terdiri dari 4 tahap menggunakan model turbulensi k-ε dengan jumlah meshing sekitar 1,690,862, seperti ICEM, preprocessor, solver dan convergence. Pada setiap pemograman, diperoleh hasil konvergensi yang lebih baik. Pada paper ini diperlihatkan hasil perhitungan dengan dan tanpa menggunakan metoda Savitsky, di mana perubahan sudut trim (τ) mempengaruhi hasil pada gaya gaya hidrodinamika versus kecepatan. Hasil penelitian ini, menjadikan pegangan Pilot untuk menggunakan perubahan sudut trim saat melakukan prosedur take off